Evaluation of Neck-shaft Angle and Anteversion in Dry Femora of Adult Indian Population: A Descriptive Analysis - Akash Hosthota; Manikandan Thandapani; N Deen M Ismail; Aravind J Devendrappa; Mohammed Shahid (Journal of Orthopedics and Joint Surgery)
Aims and background: Proximal femoral angles, specifically the neck-shaft angle (NSA) and anteversion (AV), are pivotal factors in understanding hip joint biomechanics, the changes in different hip pathologies and guiding various orthopedic interventions. Our study aims to evaluate these angles in the subcontinent of India. Materials and methods: A total of 50 dry samples of femora were selected at the Anatomy Department, Madras Medical College. Inclusion and exclusion criteria were established based on the study design. The AV and NSA were measured using three methods—direct measurement, biplanar radiography, and axial computed tomography (CT). Comparative analyzes were performed to assess the precision of these measurement techniques. Results: Our study revealed that the X-ray method was the most accurate in measuring the NSA among the three techniques. The measurements of AV were more accurate using the X-ray method than the CT method. Additionally, a prevalence of 20% for retroversion was identified in the Indian population, signifying a higher occurrence compared to prior studies. Conclusion: These findings underscore the critical importance of precise angle measurements in orthopedic hip procedures. The study's data supports informed preoperative planning and the enhancement of orthopedic interventions, particularly in the Indian population. Clinical significance: The study's findings on AV and NSA in the adult Indian population provide significant insights for orthopedic interventions, emphasizing the need for accurate measurements to enhance preoperative planning and optimize surgical outcomes.